2016
DOI: 10.1074/jbc.m115.695577
|View full text |Cite
|
Sign up to set email alerts
|

p46Shc Inhibits Thiolase and Lipid Oxidation in Mitochondria

Abstract: Although the p46Shc isoform has been known to be mitochondrially localized for 11 years, its function in mitochondria has been a mystery. We confirmed p46Shc to be mitochondrially localized and showed that the major mitochondrial partner of p46Shc is the lipid oxidation enzyme 3-ketoacylCoA thiolase ACAA2, to which p46Shc binds directly and with a strong affinity. Increasing p46Shc expression inhibits, and decreasing p46Shc stimulates enzymatic activity of thiolase in vitro. Thus, we suggest p46Shc to be a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…We saw that p46Shc was also induced in aging, which raises the question regarding its role in NASH. In fact, p46Shc dysregulated mitochondrial β-oxidation by inhibiting 3-ketoacyl-CoA thiolase, (23) thereby increasing the FFA load in hepatocytes. More work would be required to decipher the respective roles of p46 and p52Shc isoforms in NASH.…”
Section: Figmentioning
confidence: 99%
“…We saw that p46Shc was also induced in aging, which raises the question regarding its role in NASH. In fact, p46Shc dysregulated mitochondrial β-oxidation by inhibiting 3-ketoacyl-CoA thiolase, (23) thereby increasing the FFA load in hepatocytes. More work would be required to decipher the respective roles of p46 and p52Shc isoforms in NASH.…”
Section: Figmentioning
confidence: 99%
“…However, similar to skeletal muscle [8] , Shc-related changes in enzyme activity do not appear to be due to alterations in gene expression since there were no differences in the protein levels of glycolytic or gluconeogenic enzymes between ShcKO and WT mice. We have recently reported that the activity of thiolase was decreased through direct binding with p46Shc [10] and it is possible that the activities of other enzymes could be altered through binding with Shc proteins. Additional studies are needed to determine if Shc proteins bind and directly influence the activities of any enzymes in the glycolysis or gluconeogenesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of fatty acid β-oxidation enzymes in liver and skeletal muscle were also increased in ShcKO compared to wild-type mice in the fasted state, and the activities of ketogenic enzymes were increased in liver from ShcKO versus wild-type mice [9] . Moreover, we have reported recently that the β-oxidation enzyme 3-ketoacyl-CoA thiolase was directly influenced by p46Shc through binding that resulted in decreased activity and that lower levels of p46Shc resulted in increased activity of the enzyme [10] . The results of our current studies are consistent with the idea that Shc proteins may play a role in regulating substrate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In both liver and muscle, the activities of β-hydroxybutyrate dehydrogenase and acetoacetyl-CoA thiolase were increased (P < 0.05) in both the fed and fasted states in the ShcKO compared to WT mice. Overall, these results indicate that skeletal muscle from the ShcKO animals has an increased capacity for oxidizing both fatty acids and ketone bodies Tomilov et al, 2016).…”
Section: β-Oxidation and Ketone Body Metabolismmentioning
confidence: 83%
“…These results indicate that Shc proteins may influence the fuels used for energy but they do not produce a net change in overall capacity for energy metabolism in the mitochondria. Shc proteins may play an important role in energy metabolism and, particularly, a decrease in Shc levels leads to an increased capacity for β-oxidation, ketone body metabolism, amino acid catabolism and gluconeogenesis under fasting conditions Tomilov et al, 2016). Decreases in Shc proteins may play an important role in transitioning the animal from a fed to a fasted state.…”
Section: The Citric Acid Cyclementioning
confidence: 99%